Software Tools to Facilitate Systematic Review Used for Cancer Hazard Identification - Shapiro, Andrew J.; Antoni, Sébastien; Guyton, Kathryn Z.; Lunn, Ruth M.; Loomis, Dana; Rusyn, Ivan; Jahnke, Gloria D.; Schwingl, Pamela J.; Mehta, Suril S.; Addington, Josh; Guha, Neela (Environmental health perspectives, 2018)
Objective and systematic methods to search, review, and synthesize published studies are a fundamental aspect of carcinogen hazard classification. Systematic review is a historical strength of the International Agency for Research on Cancer (IARC) Monographs Program and the United States National Toxicology Program (NTP) Office of the Report on Carcinogens (RoC). Both organizations are tasked with evaluating peer-reviewed, published evidence to determine whether specific substances, exposure scenarios, or mixtures pose a cancer hazard to humans. This evidence synthesis is based on objective, transparent, published methods that call for extracting and interpreting data in a systematic manner from multiple domains, including ) human exposure, ) epidemiological evidence, ) evidence from experimental animals, and ) mechanistic evidence. The process involves multiple collaborators and requires an extensive literature search, review, and synthesis of the evidence. Several online tools have been implemented to facilitate these collaborative systematic review processes. Specifically, Health Assessment Workplace Collaborative (HAWC) and Table Builder are custom solutions designed to record and share the results of the systematic literature search, data extraction, and analyses. In addition, a content management system for web-based project management and document submission has been adopted to enable access to submitted drafts simultaneously by multiple co-authors and to facilitate their peer review and revision. These advancements in cancer hazard classification have applicability in multiple systematic review efforts. https://doi.org/10.1289/EHP4224.